Setting the top 10 priorities for obesity and weight-related research (POWeR): a stakeholder priority setting process. Issue 7 (20th July 2022) - Butler, Ailsa R; Astbury, Nerys M; Goddard, Lucy; Hajizadeh, Anisa; Seeber, Philippa; Crawley, Bruce; Aveyard, Paul; Jebb, Susan A
Abstract : Objectives: To identify and prioritise the most impactful, unanswered questions for obesity and weight-related research. Design: Prioritisation exercise of research questions using online surveys and an independently facilitated workshop. Setting: Online/virtual. Participants: We involved members of the public including people living with obesity, researchers, healthcare professionals and policy-makers in all stages of this study. Primary outcome measures: Top 10 research questions to be prioritised in future obesity and weight-related research. Results: Survey 1 produced 941 questions, from 278 respondents. Of these, 49 questions held satisfactory evidence in the scientific literature and 149 were out of scope. The remaining 743 questions were, where necessary, amalgamated and rephrased, into a list of 149 unique and unanswered questions. In the second survey, 405 respondents ranked the questions in order of importance. During the workshop, a subset of 38 survey respondents and stakeholders, agreed a final list of 10 priority research questions through small and large group consultation and consensus. The top 10 priority research questions covered: the role of the obesogenic environment; effective weight loss and maintenance strategies; prevention in children; effective prevention and treatment policies; the role of the food industry; access to and affordability of a healthy diet; sociocultural factors associated with weight; the biology of appetite and food intake; and long-term health modelling for obesity. Conclusions: This systematic and transparent process identified 149 unique and unanswered questions in the field of obesity and weight-related research culminating in a consensus among relevant stakeholders on 10 research priorities. Targeted research funding in these areas of top priority would lead to needed and impactful knowledge generation for the field of obesity and weight regulation and thereby improve population health.